2019
DOI: 10.12659/ajcr.913488
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon Presentation of Metastatic Squamous Cell Carcinoma of the Skin and Treatment Challenges

Abstract: Patient: Female, 80Final Diagnosis: Metastatic squamous cell carcinoma of skinSymptoms: Back pain • leg swelling • utiMedication: —Clinical Procedure: ImmunotherapySpecialty: OncologyObjective:Unusual clinical courseBackground:Squamous cell carcinoma is one of the most common keratinocytic skin cancers, the other being basal cell carcinoma. It is the second most common skin cancer after melanoma. Cutaneous squamous cell carcinoma is mostly a localized disease. The metastatic presentation is rare even in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…The high potential of cisPt as a chemotherapy agent against cSCC with respect to 5-fluorouracil has already been described [7]. Some other studies also suggested platinum compounds as an alternative treatment to inoperable cSCC [25]. Going one step further, the results obtained in this work showed that cisPt 3.5 μM diluted in tricine 50 mM was the most effective strategy to significantly decrease (up to~40%) cSCC cell survival with only one application.…”
Section: Discussionsupporting
confidence: 57%
“…The high potential of cisPt as a chemotherapy agent against cSCC with respect to 5-fluorouracil has already been described [7]. Some other studies also suggested platinum compounds as an alternative treatment to inoperable cSCC [25]. Going one step further, the results obtained in this work showed that cisPt 3.5 μM diluted in tricine 50 mM was the most effective strategy to significantly decrease (up to~40%) cSCC cell survival with only one application.…”
Section: Discussionsupporting
confidence: 57%
“…Recently, FDA has approved a PD-1 blockade treatment for unresectable locally advanced and metastatic cutaneous SCCs with Cemiplimab [134]. However, most patients' clinical response was partial or short-lived, and a considerable percentage of patients suffered disease progression [135]. Checkpoint inhibitors that target PD-L1 have also been approved by FDA for the treatment of metastatic NSCLC, urothelial [136,137], Merkel-cell carcinoma and advanced bladder cancer [138][139][140].…”
Section: Impact Of Tumor-infiltrating Immune Cells On Tumor Progression and Metastasismentioning
confidence: 99%
“…At present, advanced or metastatic cSCC portend a poor prognosis, with few available treatment options. Most of the literature is based on platinum therapy or cetuximab, with low overall response rates and high toxicity [6].…”
Section: Discussionmentioning
confidence: 99%